Created Impulse Buying by Shopping Lifestyle - Puspitasari, Isma; Maftukhah, Ida (Management Analysis Journal, 2019)
This research Aimed to know the effect of store atmosphere and hedonic shopping motives towards impulse buying directly and indirectly through lifestyle shopping. The population were 116 respondents from Trio Plaza Magelang’s consument. The sampling technique used non-probability sampling method, the which were 116 respondents. Methods of collecting the data using questionnaires and documentation. Data analysis using classic assumption test and hypotesys test (t test and path analysis) with SPSS Statistics 22. The research result has stated that store atmosphere positive and significant toward impulse buying, hedonic shopping motives has positive and significant toward impulse buying.